To solve for \( y \) in the equation \( 3x + 5y = 60 \), we need to isolate \( y \).
Here are the steps:
-
Subtract \( 3x \) from both sides: \[ 5y = 60 - 3x \]
-
Divide both sides by 5 to solve for \( y \): \[ y = \frac{60 - 3x}{5} \]
-
This can be simplified to: \[ y = 12 - \frac{3}{5}x \]
None of the responses you provided exactly match this form, but can be analyzed from the options listed. The option that closely resembles part of our derived formula is:
- y = 60 - 3x (where y = 60 - 3x is not divided by 5). But this isn't in accordance with our calculation.
Therefore, none of the given choices are correct based on the solved equation. However, the form of the solution \( y = \frac{60 - 3x}{5} \) can be calculated from the original equation.
Would you like to see more detailed calculations or approaches?